LEVEL OF EDUCATION WITH THE FAMILY INCOME OF MILK PRODUCERS IN THE APL LÁCTEO DO OESTE GOIANO - Clara Oliveira Costa, Aaria; Gabriele Campos Silva, Kettly; Gabrielle Borges Cruvinel, Kellita; Aurélio Souza Ramos, Marco; Teixeira da Silva, Jhonata; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2023)
Milk is among the five most sold products in the world, and the dairy market in Brazil is one of the most important segments of the industry. Small producers have a significant participation in the milk chain, although flaws in the production system and traditional techniques are responsible for stagnating the activity, especially on small properties. In addition to this, the level of education of producers is a determining factor in increasing family income. The objective of the work is to prove, through data, the impact of the level of education on the gross family income of milk producers in western Goiás. The data was collected through the application of a questionnaire to 126 producers spread across 26 municipalities in the western region of Goiás, who were questioned regarding their level of education and gross income, which was divided into salaries of up to 5 thousand reais, up to 10 thousand reais and more than 10 thousand reais. When analyzing the data, it was possible to observe the impact of individuals’ level of education on declared gross family income and indirectly relate it to the technology of the system, since of 12 of the 126 individuals who receive a gross salary above 10 thousand reais, 50% have complete higher education, and of the total of 6 illiterate individuals, 100% receive less than 5 thousand reais in gross income. The level of education is related to the gross monthly income of dairy producers, which appears to be related to the level of technical knowledge and use of technologies.